Overview Of Nutritional Status In Preschool Children At Assisi Kindegarten Medan In 2021 - Vina Yolanda Sari Sigalingging; Lilis Novitarum2; Gracya Marettha (Science Midwifery, 2022)
Nutritional status is an expression of a state of balance in the form of certain variables, or the embodiment of body status related to nutrition in the form of certain variables. This study aims to describe the nutritional status of preschool children in Assisi Kindergarten Medan in 2021. This type of research is descriptive. Sampling using Simple Random Sampling with 56 respondents. The results showed that the nutritional status of preschool children in Assisi Kindergarten in 2021 with good nutrition found that there were 22 people (33.9%) and 3 people (5.4%). The results of the univariate analysis test where there is an overview of the nutritional status of preschool children in TK Assisi Medan in 2021. It is recommended for teachers and parents of students to be able to improve and maintain good nutrition in preschool children to avoid the occurrence of nutritional status in the obesity category. Conclusion: The results of the study can be concluded that the nutritional status of preschool children is influenced by several factors in the family, namely work, income, and parental education.